2005
DOI: 10.1186/1746-1340-13-16
|View full text |Cite
|
Sign up to set email alerts
|

Reflex control of the spine and posture: a review of the literature from a chiropractic perspective

Abstract: Objective: This review details the anatomy and interactions of the postural and somatosensory reflexes. We attempt to identify the important role the nervous system plays in maintaining reflex control of the spine and posture. We also review, illustrate, and discuss how the human vertebral column develops, functions, and adapts to Earth's gravity in an upright position. We identify functional characteristics of the postural reflexes by reporting previous observations of subjects during periods of microgravity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 164 publications
(170 reference statements)
3
13
0
Order By: Relevance
“…In addition, improvement in motor performance may be attributed to the visual and proprioception input. This fact is supported by findings of Morningstar et al [22], who concluded that visual and vestibular input as well as joint and soft tissue mechanoreceptors play an important role in the regulation of static upright posture. Besides, Prokop et al [23] stated that a combination of visual and proprioceptive information is important for the modulation of walking velocity and indicates that visual information modifies stride length while proprioceptive input maintains a constant stride frequency, leading to a shift in walking velocity.…”
Section: Principal Resultssupporting
confidence: 71%
“…In addition, improvement in motor performance may be attributed to the visual and proprioception input. This fact is supported by findings of Morningstar et al [22], who concluded that visual and vestibular input as well as joint and soft tissue mechanoreceptors play an important role in the regulation of static upright posture. Besides, Prokop et al [23] stated that a combination of visual and proprioceptive information is important for the modulation of walking velocity and indicates that visual information modifies stride length while proprioceptive input maintains a constant stride frequency, leading to a shift in walking velocity.…”
Section: Principal Resultssupporting
confidence: 71%
“…Given the unique importance of these centers on reflexive neuromotor spinal control [24], disturbances in the levels of these neurotransmitters may have significant effects on spinal neuromotor output. This is supported by a previous study in which patients who participated in a chiropractic rehabilitation treatment for idiopathic scoliosis, and who also received concurrent treatment for urinary neurotransmitter imbalances, reported better follow-up outcomes at 6 months compared with patients who did not receive the neurotransmitter portion of treatment [25] [26].…”
Section: Discussionsupporting
confidence: 65%
“…Vision appears to be the primary input in terms of relating to one's position in space in infancy (Legrand et al, 2011;Morningstar et al, 2005) and balance again becomes more visually dependent with age from the mid-forties onwards (Poulain & Giraudet, 2008). There is a suggestion that it may not just be sight that is important in terms of visual input to balance.…”
Section: Sensory Integrationmentioning
confidence: 98%
“…There is a suggestion that it may not just be sight that is important in terms of visual input to balance. Proprioceptive input from extra-ocular muscles may also be an important part of the visual postural control pathway, passing through the optic tract nucleus to the superior colliculus, which has an important role in head and eye orientation and coordination (Morningstar et al, 2005). The clinical implications of the proprioceptive input from extra-ocular muscles are addressed in the section on postural instability below.…”
Section: Sensory Integrationmentioning
confidence: 99%